Maximum efficiency control and predictive-speed controller design for interior permanent magnet synchronous motor drive systems - Liu, Tian-Hua; Zhuang, Yu-Hang (Frontiers in Electronics, 2022)
Improving the efficiency of home appliances is an important area of research these days, especially in light of global warming and climate change. To achieve this goal, Several high efficiency motors and high efficiency inverters have been developed. Furthermore, improving the maximum efficiency tracking control of AC motor drives is also another feasible research direction to save energy and improve efficiency. In this paper, a method to improve the maximum efficiency control of an interior permanent magnet synchronous motor (IPMSM) drive system, which includes an IPMSM and an inverter, is investigated. By suitably controlling the d-axis current, the IPMSM drive system can quickly reach its maximum efficiency. A steepest ascent method is used to reduce the searching steps of the maximum efficiency tracking control for an IPMSM. In addition, to improve the dynamic responses of the IPMSM drive system, predictive controllers with and without an input current constraint are designed as well. A digital signal processor, manufactured by Texas Instruments, type TMS-320F-28379D, is used as a control center to achieve the maximum efficiency tracking control for the IPMSM drive system. Experimental results can validate theoretical analysis and show the correctness of the proposed method.